Hadith #2254 - Sunan Abi Dawud - Asim bin Kulayb bin Shahab عاصم بن كليب بن شهاب بن المجنون; ibn Abbas; Kulayb bin Shahab كليب بن شهاب; Mkhld bin Khalid bin Yazid مخلد بن خالد بن يزيد الشعيري; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Abi Dawud)
Ibn ‘Abbas said “Hilal bin Umayyah accused his wife in the presence of Prophet (ﷺ) of having committed adultery with Sharik bin Sahma’”. The Prophet (ﷺ) said “Produce evidence or you must receive punishment on your back.” He said “Apostle of Allaah(ﷺ) when one of us sees a man having intercourse with his wife should he go and seek evidence?” But the Prophet (ﷺ) merely said “You must produce evidence or you must receive punishment on your back.” Hilal then said “By H
Grade: Sahih

Hadith #2704 - Sunan Abi Dawud - Abu al-Ahwus, Salam bin Sulaym al-Hanafi أبو الأحوص سلام بن سليم الحنفي; Asim bin Kulayb bin Shahab عاصم بن كليب بن شهاب بن المجنون; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; Kulayb bin Shahab كليب بن شهاب (Sunan Abi Dawud)
Muhammad ibn AbulMujahid reported Abdullah ibn AbuAwfa as saying: I asked: Did you set aside the fifth of the food in the time of the Messenger of Allah (ﷺ)? He replied: On the day of Khaybar we captured food and a man would come and take as much food of it as needed and then go away.
Grade: Sahih

Hadith #2752 - Sunan Abi Dawud - Asim bin Kulayb bin Shahab عاصم بن كليب بن شهاب بن المجنون; Ibrahim bin Muhammad bin al-Harith إبراهيم بن محمد أبو اسحاق الفزاري (Sunan Abi Dawud)
Salamah (bin Al ‘Akwa) said “Abd Al rahman bin ‘Uyainah raided the Camels of the Apostle of Allaah(ﷺ) and killed their herdsman. He and some people who were with him on horses proceeded on driving them away. I turned my face towards Madeenah and shouted three times. A morning raid, I then went after the people shooting arrows at them and hamstringing them (their beasts). When a horseman returned to me, I sat in the foot of a tree till there was no riding beast of the Prophet (ﷺ) create
Grade: Hasan Sahih

Hadith #2798 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Asim bin Kulayb bin Shahab عاصم بن كليب بن شهاب بن المجنون; Kulayb bin Shahab كليب بن شهاب; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) distributed sacrificial animals among his Companions. He gave me a kid (of less than a year). I took it to him and said: This is a kid. He said: Sacrifice it. so I sacrificed it.
Grade: Hasan Sahih

Hadith #3331 - Sunan Abi Dawud - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Asim bin Kulayb bin Shahab عاصم بن كليب بن شهاب بن المجنون; Kulayb bin Shahab كليب بن شهاب (Sunan Abi Dawud)
The Prophet (ﷺ) said: A time is certainly coming to mankind when only the receiver of usury will remain, and if he does not receive it, some of its vapour will reach him. Ibn Isa said: Some of its dust will reach him.
Grade: Da'if

Hadith #3683 - Sunan Abi Dawud - Abu Barda bin Abi Musa al-Asha'ari أبو بردة / الحارث بن أبي موسى الأشعري; Abu Musa al-Asha'ari; Asim bin Kulayb bin Shahab عاصم بن كليب بن شهاب بن المجنون; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Wahb bin Bqyh bin 'Uthman وهب بن بقية بن عثمان (Sunan Abi Dawud)
I asked the Prophet (ﷺ) and said: Messenger of Allah! we live in a cold land in which we do heavy work and we make a liquor from wheat to get strength from if for our work and to stand the cold of our country. He asked: Is it intoxicating? I replied: Yes. He said: You must avoid it. I said: The people will not abandon it. He said: If they do not abandon it, fight with them.
Grade: Sahih

Hadith #4189 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Asim bin Kulayb bin Shahab عاصم بن كليب بن شهاب بن المجنون; Kulayb bin Shahab كليب بن شهاب; Mua'wiya bin Hisham al-Qsar معاوية بن هشام القصار; Sufyan bin 'Uqba al-Swa'iy سفيان بن عقبة السوائي الكوفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Wa'il bin Hujr al-Kundi al-Hadrami (Sunan Abi Dawud)
When I parted the hair of the Messenger of Allah (ﷺ) I made a parting from the crow of his head and let his forelock hang between his eyes.
Grade: Hasan

Hadith #4224 - Sunan Abi Dawud - Abu Barda bin Abi Musa al-Asha'ari أبو بردة / الحارث بن أبي موسى الأشعري; Ali ibn Abi Talib; Asim bin Kulayb bin Shahab عاصم بن كليب بن شهاب بن المجنون; Masdad bin Masrhad مسدد بن مسرهد بن مسربل (Sunan Abi Dawud)
The signet-ring of the Prophet (ﷺ) was of iron polished with silver. Sometimes it remained in my possession. Al-Mu’ayqib was in charge of the signet-ring of the Prophet (ﷺ).
Grade: Hasan

Hadith #4839 - Sunan Abi Dawud - Abdul Wahid bin Ziyad عبد الواحد بن زياد العبدي; Abu Hurairah; Asim bin Kulayb bin Shahab عاصم بن كليب بن شهاب بن المجنون; Kulayb bin Shahab كليب بن شهاب; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) spoke in a distinct manner so that anyone who listened to him could understand it.
Grade: Hasan Sahih